2020
DOI: 10.1186/s11782-020-00079-1
|View full text |Cite
|
Sign up to set email alerts
|

How does the servant supervisor influence the employability of postgraduates? Exploring the mechanisms of self-efficacy and academic engagement

Abstract: Drawing on the conservation of resource theory, this study investigates the mediating effects of self-efficacy and academic engagement in the relationship between servant supervision and postgraduates’ employability. We conducted a field study with 598 postgraduates (students for the research-based master's degree and PhD candidates) enrolled in universities in China to test our hypotheses. We developed and tested a model contending that servant supervisors propagate servant supervision among postgraduates thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 84 publications
4
14
0
Order By: Relevance
“…The results indicate that there was a significant positive relationship among general self-efficacy, achievement motivation, career aspirations, and employability. Specifically, consistent with existing research, this study confirms that general self-efficacy positively predicted employability (Zhong et al, 2020), via achievement motivation (Chemers et al, 2001;Torres and Solberg, 2001), and also facilitated the establishment of career aspirations (Mau and Li, 2018).…”
Section: Conclusion Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results indicate that there was a significant positive relationship among general self-efficacy, achievement motivation, career aspirations, and employability. Specifically, consistent with existing research, this study confirms that general self-efficacy positively predicted employability (Zhong et al, 2020), via achievement motivation (Chemers et al, 2001;Torres and Solberg, 2001), and also facilitated the establishment of career aspirations (Mau and Li, 2018).…”
Section: Conclusion Discussionsupporting
confidence: 89%
“…A previous study found that individuals' role breadth self-efficacy was positively related to their perceived employability (Hanzla et al, 2019). Besides that, researchers have explored the relationship between self-efficacy and employability using Chinese postgraduate students as subjects and suggested that selfefficacy positively predicted employability (Zhong et al, 2020). Moreover, Yan et al (2019) found that university students' self-efficacy in career decision-making positively predicted employability.…”
Section: General Self-efficacymentioning
confidence: 99%
“…Individuals use their key resources to cope with stressful situations in the current environment and they also actively construct and protect the existing resources to deal with possible stressful situations in the future. Self-control and self-efficacy are typical individual resources (Hagger et al, 2010 ; Guarnaccia et al, 2018 ; Zhong et al, 2020 ). Self-control refers to the self-suppression of harmful reaction tendency and self-stimulation of beneficial reaction tendency through cognitive, emotional and behavioral strategies (Hagger et al, 2010 ; Righetti and Finkenauer, 2011 ).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Among the exogenous variables, self-efficacy has affected the endogenous variable directly and indirectly. The variable's indirect effect passes through the level of competency, finally affecting the employability of graduates (Ahmed et al, 2019;Zhong et al, 2020). The second path has directly affected the employability of graduates with the coefficient of 0.146 and a statistically significant p value = 0.006 (Caballero et al, 2017;Ahmed et al, 2019;Zhong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…When they develop self-efficacy, they become self-confident and motivated to convince the employers (Caballero et al, 2017). Thus, there is a positive relationship between self-efficacy and enhanced competency of students and the employability of graduates (Ahmed et al, 2019;Zhong et al, 2020). Accordingly, the above discussion helps us to develop the following hypothesis: H 3 : Self-Efficacy Has a Positive Statistically Significant Effect on the Employability of Business Graduates H 4 : Self-Efficacy Has a Positive Statistically Significant Effect on the Graduate Level of Competency of Business Graduates…”
Section: University Reputation Has a Positive Statistically Significa...mentioning
confidence: 99%